Restorative justice for adult offenders in South Australia: judicial perspectives and insights - Marsland, Corrine (Contemporary justice review, 2024)
Restorative justice seeks to address harms arising from criminal conduct, with a focus that extends beyond punishment. While Australia has embraced restorative justice practices for young and Aboriginal and Torres Strait Islander offenders, programs for adult offenders have been comparatively slow to progress. Despite the reliance on judicial officers as the primary referral mechanism, there is limited research examining their views of restorative justice, particularly in the context of adult offenders. This paper presents the findings from a survey and interviews with judicial officers in one Australian jurisdiction: South Australia. There was clear support for restorative justice measures for adult offenders for a broad range of offences. Some concerns were raised with respect to victims’ safety, and the additional time and resources that restorative justice expends. Overall, the study found that the judicial officers who participated would welcome the introduction of a restorative justice program for adult offenders. With this support, and the potential benefits of restorative justice for victims, offenders, and the community, South Australia should consider extending its restorative justice offerings to adult offenders.